Economic Implications of the Application of Value Added Tax in Sudan - Mohammed, Abdulrahman Omar Ahmed; Aljali, Abdul Wahab Mousa (Journal of Economic, Administrative and Legal Sciences, 2017)
The study aimed to investigate the economic implications underlying the implementation of value added tax. To achieve this objective, descriptive analytical method is found to be more is found to be more applicable to this research. Hundred (100) questionnaires were distributed to population and with 92% effective rate of responses Results were processed by using SPSS. The main finding is that implementing value added tax increases public financial resources. Further, there is a strong relationship between unifying tax regulation. The use of VAT .The study recommended more researches in this topic and the necessity to exempt goods and services from taxes while protecting contributors against potential drawbacks of VAT.